(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article analyzes the economic activities and theoretical views of Adam Smith, the founder of the classical school of political economy, in the era of manufacturing. The study broadly covers Smith’s scientific activities as an economist, his experience in public administration, and his views on the division of labor, the market mechanism, and economic freedom. It also analyzes the modern assessments of Adam Smith’s teachings by Uzbek economists and their significance in the development of a market economy. The article serves to reassess Adam Smith as the theoretical founder of the economy of the era of manufacturing.